The Study on Large-Diameter Drilling Prevention Method of Rock Burst in the Xinxing Coal. (8th May 2021) - Xu, Gao; Minghui, Zuo; Yanmin, Shu
Abstract : Based on the engineering background, the 41051 working face of the 65th coal mine in Qitaihe Xinxing Mine was regarded as the engineering background, by using of the comprehensive research methods such as theoretical analysis and calculation, FLAC3D numerical simulation, physical parameters of coal and rock in laboratory, and the field industrial measurement, to research on the large drilling relieving rock burst mechanism and parameter setting in reasonable. The distribution of stress and plastic zone in drilling surrounding rock and its influence parameters are clarified, and the distribution of the "butterfly plastic zone" and the mutation condition of the "butterfly plastic zone" in trigger stress state are explored. On the basis, combined with theoretical analysis and numerical simulation, studying the rock burst prevention and treatment mechanism in large drilling, through the statistics of the Xinxing mine pressure characteristics, the measurement of the physical parameters of coal and rock and the test of ground stress finding is that the coal satisfies "Three hard" condition in Xinxing mine and is affected by larger horizontal tectonic stress. Combined with the real geological conditions, the layout parameters of relief pressure large drilling are simulated, and the result shows that the drilling of 600 diameters and 10 m pitch of hole and throughout the working face is reasonable, and the effect is obvious about pressure relief. For the practical implementation, the electromagnetic radiation monitoring is used to evaluate the effect in field; to comprehensive analysis, the relief pressure large drilling has obvious control effect to the 41051 workface rock burst.